DESIGN OF ENTERPRISE ARCHITECTURE IN E-GOVERNMENT DEVELOPMENT USING TOGAF ADM 9.2 FRAMEWORK IN ELECTRICITY SECTOR OF DEPARTMENT ENERGY AND MINERAL RESOURCE OF WEST JAVA PROVINCE - Adam Satya Kencana; Asti Amalia Nur Fajrillah; Ridha Hanafi (STKIP PGRI Tulungagung, 2022)
Over the past few years, the Government has used information and communication technology to integrate its internal functions and improve service delivery. As part of the West Java Provincial Government, the Department of Energy and Mineral Resources has an active role in the West Java provincial government. The West Java Government's target is to improve electrical energy infrastructure that supports economic growth and access to electricity for households in remote areas so that they can contribute to improving electronic-based government system services in West Java Province. This research will be aimed at helping the effectiveness and efficiency of public services through the design of Enterprise Architecture (EA). This research will focus on business processes, data and information, applications, and services (excluding infrastructure and security). The final result of this research is an EA design blueprint that contains proposed solutions for business process improvements, data integration, application development, and fulfillment of public service needs concerning the Electricity Sector of the West Java Province ESDM Department in the hope of facilitating access to electricity services in West Java.